Alternate hosts of African cassava mosaic virus and East African cassava mosaic Cameroon virus in Nigeria - Alabi, O.J.; Ogbe, F.O.; Bandyopadhyay, Ranajit; Kumar, P. Lava; Dixon, Alfred G.O.; Hughes, Jacqueline d'Arros; Naidu, R.A. (Springer, 2008)
Cassava mosaic disease (CMD) caused by African cassava mosaic virus (ACMV) and East African cassava mosaic Cameroon virus (EACMCV) is the major constraint to cassava production in Nigeria. Sequences of the DNA-A component of ACMV and EACMCV isolates from leguminous plant species (Senna occidentalis, Leucana leucocephala and Glycine max), castor oil plant (Ricinus communis), a weed host (Combretum confertum) and a wild species of cassava (Manihot glaziovii) were determined. All ACMV isolates from these hosts showed 96–98% nucleotide sequence identity with cassava isolates from West Africa. EACMCV was found only in four hosts (S. occidentalis, L. leucocephala, C. confertum, M. glaziovii), and sequences of these isolates showed 96–99% identity with cassava isolates from West Africa. These results provide definitive evidence for the natural occurrence of ACMV and EACMCV in plant species besides cassava.